Analysis of Student Learning Media Development in Schools Using the ADDIE Method - Yulianssyah, Andree (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
The development of science and technology increasingly encourages renewal efforts in the use of technological results in the learning process. The use of computer technology in schools is still not optimal, especially in mathematics subjects. Where mathematics subjects really need technological tools to make it easier for students to understand the material in these subjects because the material contained in mathematics subjects is difficult to understand. To make it easier for students to understand mathematics subjects, learning media using PPT and VBA as well as Sparkol Videoscribe are needed using the ADDIE method. The ADDIE method is a method that carries out analysis, design, development, implementation and evaluation related to mathematics subjects so that students can understand them easily. The results of this research and development are 92% of the "Very Appropriate" category which has been analyzed by media experts and 95% of the "Very Appropriate" category which has been analyzed by material experts.